2020
DOI: 10.3389/fpls.2020.00137
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Deficiency in Sinorhizobium meliloti Does Not Impair Bacteroid Differentiation But Induces Early Senescence in the Interaction With Medicago truncatula

Abstract: Under nitrogen-limiting conditions, legumes are able to interact symbiotically with bacteria of the Rhizobiaceae family. This interaction gives rise to a new organ, named a root nodule. Root nodules are characterized by an increased glutathione (GSH) and homoglutathione (hGSH) content compared to roots. These low molecular thiols are very important in the biological nitrogen fixation. In order to characterize the modification of nodule activity induced by the microsymbiont glutathione deficiency, physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Further examples of stress responses include glutathione S-transferases, which were consistently upregulated in bacteroids. Mutants unable to produce glutathione, an important antioxidant molecule, showed reduced symbiotic efficiency (121,122). Similarly, enzymes involved in detoxification of reactive oxygen species, such as superoxide dismutases and catalases, were commonly upregulated in agreement with the presence of reactive oxygen species due to autooxidation of leghemoglobin and ferredoxin (123).…”
Section: Adaptations To Nitrogen Fixationmentioning
confidence: 99%
“…Further examples of stress responses include glutathione S-transferases, which were consistently upregulated in bacteroids. Mutants unable to produce glutathione, an important antioxidant molecule, showed reduced symbiotic efficiency (121,122). Similarly, enzymes involved in detoxification of reactive oxygen species, such as superoxide dismutases and catalases, were commonly upregulated in agreement with the presence of reactive oxygen species due to autooxidation of leghemoglobin and ferredoxin (123).…”
Section: Adaptations To Nitrogen Fixationmentioning
confidence: 99%
“…Furthermore, GSH has been shown to be crucial in nodule functioning. In most cases, gshB mutants produced abnormal nodules with a strong nitrogen-fixation deficiency, correlated with the early senescence of nodules and bacteroids [74][75][76][77][78]. In line with these findings, the recycling of GSH by glutathione reductase was also shown to be involved in nodulation and in nitrogen fixation ability [79].…”
Section: The Role Of Bacterial Gsh/grx Systemmentioning
confidence: 59%
“…vulgaris interaction, GSH deficiency was also associated with increased production of superoxide anion [77]. Regarding the interaction between S. meliloti and M. truncatula, a combination of physiological, and molecular markers, microscopic and flow cytometry analyses, showed that a gshB mutant undergoes complete differentiation before being engaged in an early senescence process [75]. Totally, these results underline the importance of the bacterial GSH/GSSG redox couple for adaptation to the host-plant environment and survival inside the host cells (Table 1).…”
Section: The Role Of Bacterial Gsh/grx Systemmentioning
confidence: 99%
“…Many additional S. meliloti mutants are described with symbiotic phenotypes that are suggestive for a similar contribution to NCR resistance. (26,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). In addition, other genes that could be important for symbiosis, were discovered in a Tn-seq screen with the peptide NCR247 (25).…”
Section: Multiple Functions Of Sinorhizobium Meliloti Contribute To Ncr Resistance and Are Required For Bacteroid Formation And Persistenmentioning
confidence: 99%